The Effect of Endsars Protest on Small and Medium Enterprises (Sme’s) In Lagos State - Godswill Akhimien, Prince (International Journal of Scientific Research and Management (IJSRM), 2022)
This study is centered on the effect of EndSars protest on small and medium enterprises (SME’S) in Lagos State. The specific objectives of this study are to examine the causes of the EndSars protest among youths in Lagos State; and also, to find out if the EndSars protest has any effect on Small and Medium Enterprises in Lagos State. Three hypotheses were drawn from the research questions and a self-administered questionnaire was used to measure the relationship between the variables using the filled questionnaires of 350 respondents of entrepreneurs in Ikeja Local Government Council. The analysis of collected data was done through the simple percentage and used Pearson Product Moment Correlation Analysis to test the hypothesis within the study. It was found that that there is a significant positive relationship between EndSars protest and SME among Nigerian youths in Lagos state also there is a significant positive relationship between causes of EndSars protest and Small and Medium Enterprises in Lagos state. Based on the findings, the study concluded that EndSars protest and Nigerian youths affect SME in Nigeria. It was therefore recommended that the federal government of Nigeria should look into the reasons behind the protest that caused chaos and uproar in all the 36 states in Nigeria and enact laws and structures that bring to an end the brutality of SARS in Nigeria.